2012
DOI: 10.1017/s2045796012000522
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Italian version of the Functioning Assessment Short Test (FAST) for bipolar disorder

Abstract: Aim. The Functioning Assessment Short Test (FAST) is a useful instrument for the assessment of overall functioning of people with bipolar disorder, showing good psychometric properties. The aim of this study is to validate the Italian version of FAST. Methods. Translation and back-translation of the original FAST Spanish version were performed. Participants with bipolar disorder (n = 132) and healthy controls (n = 132) completed the FAST as a part of an assessment package including the Montgomery-Asberg Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…In addition to Spanish and English, the FAST has been translated into Italian (Moro et al 2012 , Barbato et al 2013 ), Portuguese (Cacilhas et al 2009 ), and Turkish (Aydemir and Uykur 2012 ) and now also Finnish. The psychometric properties of the Finnish version of FAST showed high internal consistency, in accord with earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to Spanish and English, the FAST has been translated into Italian (Moro et al 2012 , Barbato et al 2013 ), Portuguese (Cacilhas et al 2009 ), and Turkish (Aydemir and Uykur 2012 ) and now also Finnish. The psychometric properties of the Finnish version of FAST showed high internal consistency, in accord with earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have healthy controls to analyse the scale’s capacity to discriminate between patients and controls. However, previous studies have examined this and have reported the optimal cutoff on the FAST total score for discriminating patients from controls to be 11 (Rosa et al 2007 , Moro et al 2012 ) or 15 (Barbato et al 2013 ). The sample size of the study was also modest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A FAST é uma entrevista estruturada e breve que aborda seis domínios de forma independente: autonomia, funcionamento ocupacional, funcionamento cognitivo, relacionamento interpessoal e tempo livre. A escala foi validada para diversas populações (Suominen et al 2015, Barbato et al 2013) incluindo a brasileira (Cacilhas et al 2009). Os escores da FAST já foram correlacionados com os mais variados desfechos, desde estigma (Vázquez et al 2011), impulsividade (Jiménez et al 2012) e abuso de substâncias .…”
Section: Recuperação Clinica E Prejuízos Funcionais No Tbunclassified